PENINGKATAN PUBLIC SPEAKING KADER PEMBINAAN KESEJAHTERAAN KELUARGA (PKK) MELALUI OLIMPIADE STUNTING - Prasanti, Ditha; Ratna Suminar, Jenny; Fuady, Ikhsan (Mafaza : Jurnal Pengabdian Masyarakat, 2024)
Stunting is still a hot topic and the main target of the Indonesian Ministry of Health in order to achieve the Golden Indonesia 2024. PKK cadres are the main drivers who play an important role in supporting the success of health programmes in a village. In this case, PKK cadres spread across Citeras, Garut can be said to be the driving force in preventing stunting. The purpose of PPM activities is to increase the competence of PKK cadres in an effort to reduce stunting rates in the Garut area. PPM activities were packaged through Stunting Olympics activities, where there was a ‘Public Speaking’ competition. The competition was attended by PKK cadres spread across Garut which was carried out at the Citeras Health Centre. In this case, Puskesmas Citeras is also a partner of the author's continuous service. This is a positive and interesting activity, where we can be directly involved in interacting with the cadres. The methods used in this community development programme are interactive methods, lecture methods, training, and discussion methods. The author also listens to every presentation of the cadres who practice public speaking competencies on socialising stunting prevention to the local community. The author provides feedback and then motivates the improvement of cadres' public speaking in the socialisation of stunting prevention. The results and achievements of the PPM activities are as an evaluation that can improve the public speaking competencies that cadres should have. The implications of this PPM activity for the community have become a valuable event for cadres in improving public speaking competencies. Likewise, the implications for communication science can also be a reference about the usefulness of public speaking material for the design of other similar PPM activities.